Cardiac Implications of COVID-19 in Deceased and Recovered Patients: A Systematic Review - Khanal, Rajaram; Raj Bhattarai, Shreeyash; Basnet, Kriti; Shah, Sangam; Dhital, Roman; Kumar Sah, Sanjit; Poudel, Sujan; Frontela, Odalys; Michel, George; Marzban, Sima; Rodriguez-Morales, Alfonso J. (Interdisciplinary Perspectives on Infectious Diseases, 2022)
Background. Patients infected with coronavirus disease 2019 (COVID-19) present with various clinical presentations with majority of them developing pulmonary complications. This study focuses on cardiac implications of COVID-19 which are less discussed and thus will help to address cardiac implications of COVID-19. Methods. PubMed, PubMed Central, and Google Scholar were screened for articles which mentioned cardiac implications of COVID-19. NHLBI Study Quality Assessment Tools for the observational cohort and cross-sectional studies was used for assessing the risk of bias of our studies. Results. All 14 studies selected were good and had score of ≥9 by NHLBI Study Quality Assessment Tools. Cardiac complications of COVID-19 are common. They are associated with significant mortality. Also, people infected with COVID-19 with premorbid conditions such as cardiovascular diseases and diabetes mellitus have poor prognosis as compared to those without premorbid conditions. Cardiac biomarkers such as highly sensitive troponin I, creatinine, and creatinine kinase-MB on admission are good prognostic markers. Conclusions. Cardiac complications such as heart failure, myocardial injury, and arrhythmias are common among patients infected with COVID-19. Elevated cardiac markers and patients with cardiac complications require utmost care and continuous cardiac monitoring.